MORPHOLOGY OF A NEW HETEROCAPSA SPECIES (PERIDINIALES, DINOPHYCEAE) OCCURED IN HUE, VIETNAM - Iwataki, Mitsunori; Kawami, Hisae; Nguyen, Nguyen van; Doc, Luong Quang; Phap, Ton That; Fukuyo, Yasuwo; Matsuoka, Kazumi (Marine Research in Indonesia, 2007)
To investigate the distribution of Heterocapsa including a harmful species H. circularisquama, cells were surveyed in three Vietnamese coasts, Ha Long Bay, Hue and Phu Quoc Island in 2006. Cells of Heterocapsa were detected from Lang Co Lagoon and adjacent coast in Hue. Cell of the species possesses thecal plates corresponding to the typical of Heterocapsa. Under TEM, body scales approximately 500 nm in diameter are observed. The scale structure is similar to that of H. illdefina, however, number of the marginal spine is different. We concluded it is an undescribed Heterocapsa species possessing a new body scale ultrastructure.